Aortic plaques in patients with atrial fibrillation: an often-forgotten risk factor for thromboembolism. (14th October 2021) - Esteves, A.F; Parreira, L; Fonseca, M; Farinha, J.M; Ferreira, J; Pinheiro, A; Coelho, R; Mesquita, D; Amador, P; Lopes, A; Fonseca, N; Caria, R
Abstract: Background: CHA2DS2-VASc risk score is the main determinant for maintaining anticoagulation after atrial fibrillation (AF) ablation, irrespective of the procedure outcome. The presence of aortic plaques is included in the score, but isn't regularly assessed previously to AF ablation. This way, risk factors for coronary artery disease (CAD) other than arterial hypertension and diabetes mellitus may influence stroke risk in patients with AF, albeit not being included in the CHA2DS2-VASc score. Purpose: We sought to evaluate the prevalence of aortic plaques diagnosed during transesophageal echocardiography (TOE) in patients submitted to AF ablation and to assess its determinants and clinical impact on the CHA2DS2-VASc score. Methods: Retrospective study of patients submitted to AF ablation that performed TOE prior to the procedure, with assessment of aortic plaques. CHA2DS2-VASc risk score was evaluated in the pre-ablation patient evaluation and reassessed after TOE. Demographic, clinical and echocardiographic data, including cardiovascular risk factors, were analyzed. We assessed AF recurrence rate, cerebrovascular events and death during follow-up. Results: 120 patients were submitted to TOE prior to AF ablation from November 2015 to December 2020, mean age 66.6 (±9.55) years, 48% male. In 30 (25%) patients aortic plaques were identified in TOE. Mean CHA2DS2-VASc was 2.2 (±1.47) in pre-ablation evaluation and 2.5 (±1.69) post-TOE, increasing in all patients with aortic plaques and prompting beginning of oral anticoagulation in 5 patients. AF was paroxysmal in 74% and persistent in 26% of patients, mean duration of 6.28 (±3.76) years. Arterial hypertension was present in 79 (66%) of patients, type 2 diabetes mellitus in 24 (20%) and dyslipidemia in 67 (56%). 17 (14%) patients had a prior stroke. During a mean follow-up of 30 (±18.3) months, 32 (27%) patients had AF recurrence and 10 (8%) were submitted to redo procedures. 107 (89%) patients remained under oral anticoagulation, stroke occurred in 1 patient and 2 patients died. In univariate analysis, age, type 2 diabetes mellitus and dyslipidemia predicted an increase in CHA2DS2-VASc score after TOE (respectively, OR 1.113, 95% CI 1.041–1.190, p-value 0.002; OR 2.907, 95% CI 1.145–7.379, p-value 0.025; and OR 2.442, 95% CI 1.016–5.868, p-value 0.046). In multivariate analysis, age is the only independent predictor of increased CHA2DS2-VASc score after TOE (OR 1.095, 95% CI 1.013–1.185, p-value 0.023). No risk factor for CAD was independently associated with the presence of aortic plaques (Table 1). Conclusion: In this population, single CAD risk factors were not independent predictors of aortic plaques. If TOE had not been performed prior to AF ablation, 25% of patients would have had an underestimated CHA2DS2-VASc score and would be off anticoagulation after the procedure, unprotected from thromboembolic events. Funding Acknowledgement: Type of funding sources: None.